Polyurethane adhesive for copper clad laminate and preparation method thereof

By preparing polyurethane adhesives with flame retardant properties and tensile resistance, the problem of insufficient flame retardant properties of polyurethane adhesives in the prior art is solved, and effective fire protection and performance improvement of copper clad plates are achieved.

CN115926097BActive Publication Date: 2025-03-25KINGBOARD (GUANGZHOU) HIGH NEW MATERIAL CO LTD

Patent Information

Application Number
CN202211685419.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-03-25
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

The existing polyurethane adhesives have low flame retardant properties and cannot effectively protect copper clad plates.

Method used

The flame retardant was prepared by reacting chloromethyl (dimethyl)silane and tris(2-hydroxyethyl) isocyanurate, and reacting with polydiethylene adipate and 4,4'-dicyclohexylmethane diisocyanate, and then blocked with hydroxyethyl acrylate and photoinitiator to obtain a polyurethane adhesive for copper clad plate.

Benefits of technology

The flame retardant and tensile properties of polyurethane adhesives are improved, forming a crosslinking network structure, and it is easier to form a silicon dioxide layer to isolate oxygen and heat at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0004019555850000031
    Figure BDA0004019555850000031
Patent Text Reader

Abstract

The invention discloses a polyurethane adhesive for copper clad laminates and a preparation method thereof, and relates to the technical field of adhesives. When preparing the polyurethane adhesive for copper clad laminates, the present invention first reacts chloromethyl (dimethyl) silane with tris (2-hydroxyethyl) isocyanurate, and then reacts with diallyl tetramethyl disiloxane to obtain a flame retardant; 4-chlorobenzophenone and p-hydroxythiophenol are reacted to obtain a photoinitiator; the flame retardant, poly (diethylene glycol adipate) and 4,4'-dicyclohexylmethane diisocyanate are reacted, and then end-capped with hydroxyethyl acrylate and a photoinitiator to obtain the polyurethane adhesive for copper clad laminates. The polyurethane adhesive for copper clad laminates prepared by the present invention has excellent flame retardant properties and tensile properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a polyurethane adhesive for copper clad laminates and a preparation method thereof. Background Art

[0002] Copper clad laminate is a plate-like material made by impregnating electronic glass fiber cloth or other reinforcing materials with resin, covering one or both sides with copper foil and hot pressing. It is called copper clad laminate, or copper clad laminate for short. As the substrate material in the manufacture of printed circuit boards, copper clad laminate mainly plays the role of interconnection, insulation and support for printed circuit boards, and has a great influence on the transmission speed, energy loss and characteristic impedance of signals in the circuit. Therefore, the performance, quality, processability, manufacturing level, manufacturing cost, long-term reliability and stability of printed circuit boards depend to a large extent on copper clad laminates, and the performance of copper clad laminates depends to a large extent on adhesives.

[0003] Polyurethane is an adhesive with adjustable hardness, good flexibility and good performance at low temperatures. It has high adhesion and good bonding ability with various materials such as metals and non-metals. It is its excellent performance that makes it more and more widely used. However, the flame retardant performance of polyurethane adhesive is low and cannot provide good fire protection for copper clad laminates. Therefore, research on polyurethane adhesives with good flame retardant effects is of great value to the development of the copper clad laminate industry. Summary of the invention

[0004] The object of the present invention is to provide a polyurethane adhesive for copper clad laminates and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a polyurethane adhesive for a copper clad laminate comprises the following preparation steps:

[0007] (1) reacting chloromethyl (dimethyl) silane with tris (2-hydroxyethyl) isocyanurate, and then reacting with diallyltetramethyldisiloxane to obtain a flame retardant;

[0008] (2) reacting 4-chlorobenzophenone and p-hydroxythiophenol to obtain a photoinitiator;

[0009] (3) The flame retardant, polyethylene glycol adipate and 4,4′-dicyclohexylmethane diisocyanate are reacted, and then capped with hydroxyethyl acrylate and a photoinitiator to prepare a polyurethane adhesive for copper clad laminates.

[0010] As an optimization, the preparation method of the polyurethane adhesive for copper clad laminates comprises the following preparation steps:

[0011] (1) Preparation of flame retardant: Dissolve chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate in dioxane with a mass of 60 to 80 times that of chloromethyl (dimethyl) silane, add sodium hydroxide with a mass of 0.1 to 0.2 times that of chloromethyl (dimethyl) silane, stir at 75 to 80° C. and 800 to 1000 r / min in a nitrogen atmosphere for 6 to 8 hours, add 3 to 5% hydrochloric acid with a mass fraction of 100 to 200 times that of chloromethyl (dimethyl) silane, and cool to 3 to 40 ° C. 5℃, filter and wash with anhydrous ethanol and pure water for 3 to 5 times, dry at 30 to 40℃, 1 to 2kPa for 10 to 12h, then place in n-hexane with a mass of 20 to 30 times of chloromethyl (dimethyl) silane, add diallyltetramethyldisiloxane and a catalyst with a mass of 0.03 to 0.05 times of chloromethyl (dimethyl) silane, stir and reflux at 70 to 80℃, 500 to 800r / min for 4 to 6h, and stand at 20 to 30℃, 1 to 2kPa for 3 to 4h to obtain a flame retardant;

[0012] (2) Preparation of photoinitiator: 4-chlorobenzophenone, potassium hydroxide, toluene and N-methylpyrrolidone were mixed uniformly in a mass ratio of 1:0.2:12:4 to 1:0.3:16:6, and then an equal molar amount of p-hydroxythiophenol was added to 4-chlorobenzophenone, and stirred at 10 to 30°C and 300 to 500 r / min for 20 to 30 min to carry out a solvothermal reaction, and then 6 to 8 times the mass of 6 to 8% hydrochloric acid was added at a rate of 1 to 2 mL / min to the reaction solution at 0 to 3°C stirred at 300 to 500 r / min, and ultrasonicated at 30 to 40 kHz for 20 to 30 min, filtered, washed with pure water and petroleum ether for 3 to 5 times respectively, and dried at -10 to -1°C and 1 to 10 Pa for 6 to 8 hours to prepare a photoinitiator;

[0013] (3) Polymerization: Hydroxyethyl acrylate, photoinitiator, and dibutyltin dilaurate are mixed uniformly at a mass ratio of 1:0.2:0.1 to 1:0.3:0.2 as a capping mixed reagent; flame retardant, polyethylene glycol adipate, and 1,6-hexanediol diacrylate are mixed uniformly at a mass ratio of 1:1:4 to 1:1:6, stirred at 10 to 20°C and 300 to 500 r / min for 10 to 12 minutes, heated to 35 to 45°C, and 0.2 to 0.3 times the mass of the flame retardant is added every 15 minutes. 4,4'-dicyclohexylmethane diisocyanate, and monitor the progress of the reaction until the measured isocyanate content is 40-50% of the added isocyanate content and does not change after the delayed reaction, raise the temperature to 65-75°C and add 0.1-0.2 times the mass of the flame retardant end-capping mixed reagent every 15 minutes, monitor the progress of the reaction until the measured isocyanate content is 0.1-0.3% of the added isocyanate content, stop the reaction, and naturally cool to room temperature to obtain the polyurethane adhesive for copper clad laminates.

[0014] As an optimization, the molar ratio of chloromethyl (dimethyl) silane, tris (2-hydroxyethyl) isocyanurate and diallyltetramethyldisiloxane in step (1) is 1:1:1.

[0015] As an optimization, the catalyst in step (1) is divinyltetramethyldisiloxane platinum salt.

[0016] As an optimization, the molecular structure of the flame retardant in step (1) is as follows:

[0017]

[0018] As an optimization, the method of the solvent thermal reaction in step (2) is: placing in a high-pressure reactor lined with polytetrafluoroethylene and closing the seal, heating to 120-130°C and maintaining for 3-4 hours, continuing to heat to 160-170°C and maintaining for 3-4 hours, cooling to room temperature and opening the reactor.

[0019] As an optimization, the molecular structure of the photoinitiator in step (2) is as follows:

[0020]

[0021] As an optimization, the model of the polydiethylene glycol adipate in step (3) is PDEGA3000.

[0022] As an optimization, the method for monitoring isocyanate groups in step (3) is as follows: accurately take an appropriate amount of sample, add acetone, dissolve it, add a certain amount of 0.1 mol / L acetone-di-n-butylamine solution, shake it well and let it stand for a period of time. If necessary, it can be heated, and titrated with a standard hydrochloric acid solution. The end point is when the solution changes from blue to yellow. Bromocresol green is used as an indicator to perform a blank titration. The formula for the unreacted isocyanate group content is as follows:

[0023] w%=(V0-V)*c*4.202 / m

[0024] Where: V0---the volume of hydrochloric acid lost by the sample in the blank experiment, unit: ml;

[0025] V---volume of hydrochloric acid lost by the sample, in ml;

[0026] c---Concentration of hydrochloric acid standard solution, unit mol / L;

[0027] m---sample mass, unit: g.

[0028] As an optimization, when the polyurethane adhesive for copper clad laminate is used to prepare copper clad laminate, a 300-400W high pressure mercury lamp is used to irradiate 2-3cm above the surface of the coated polyurethane adhesive for 40-50s.

[0029] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0030] When preparing the polyurethane adhesive for copper clad laminates, the present invention firstly reacts a flame retardant, polyethylene glycol adipate and 4,4'-dicyclohexylmethane diisocyanate, and then performs end-capping with hydroxyethyl acrylate and a photoinitiator to obtain the polyurethane adhesive for copper clad laminates.

[0031] Firstly, the flame retardant and photoinitiator prepared by the present invention can be used as the chain segments of polyurethane, and can be chemically combined with the main body of polyurethane, thereby avoiding pollution or performance degradation caused by the addition and loss of small molecular organic matter; chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate are reacted, and then reacted with diallyltetramethyldisiloxane to obtain the flame retardant, and the prepared flame retardant has a relatively long silicon-carbon chain segment, and the edge has a carbon-carbon double bond, which can participate in the polymerization of free radicals initiated by the photoinitiator, so that the carbon-carbon double bonds at the edge are cross-linked and polymerized, so that the main body forms a cross-linked network structure, thereby improving the tensile performance, and the flame retardant is interspersed and combined in the structure of the main material, and it is easier to form a silicon dioxide layer at high temperature to isolate oxygen and heat, thereby improving the flame retardant performance.

[0032] Secondly, 4-chlorobenzophenone and p-hydroxythiophenol are reacted to prepare a photoinitiator. P-hydroxythiophenol replaces the chlorine on 4-chlorobenzophenone to form p-hydroxyphenylthio. Sulfur is an electron-rich atom. The donating property of the sulfur bond will affect the carbonyl group of the benzophenone main body, thereby affecting the hydrogen abstraction ability of the benzophenone main body. Secondly, the sulfide bond can be broken under ultraviolet light to produce two free radicals, which trigger the free radical polymerization of the unsaturated bond, improve the response range and response speed to ultraviolet rays, and the degree of free radical polymerization, thereby improving the tensile properties. . DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the polyurethane adhesive for copper clad laminates prepared in the following examples are as follows:

[0035] Flame retardant properties: The polyurethane adhesive for copper clad laminates obtained in each embodiment and the comparative material were applied to a polytetrafluoroethylene mold with the same mass. A 400W high-pressure mercury lamp was used to irradiate 2 cm above the coated polyurethane adhesive surface for 40 seconds. The adhesive was allowed to stand for 3 days to form a dry adhesive sample. The limiting oxygen index was tested according to GB / T2406.

[0036] Tensile performance: The polyurethane adhesive for copper clad laminates obtained in each embodiment and the comparative material were applied to a polytetrafluoroethylene mold with the same mass. A 400W high-pressure mercury lamp was used to irradiate 2 cm above the coated polyurethane adhesive surface for 40 seconds. The adhesive was allowed to stand for 3 days to form a dry adhesive sample, and the tensile strength was tested according to GB / T528.

[0037] Example 1

[0038] A method for preparing a polyurethane adhesive for a copper clad laminate, the method for preparing the polyurethane adhesive for a copper clad laminate mainly comprising the following preparation steps:

[0039] (1) Preparation of flame retardant: Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate were dissolved in dioxane (60 times the mass of chloromethyl (dimethyl) silane) in a molar ratio of 1:1, and then sodium hydroxide (0.1 times the mass of chloromethyl (dimethyl) silane) was added. The mixture was stirred at 75°C and 800 r / min for 8 h in a nitrogen atmosphere. 5% hydrochloric acid (100 times the mass of chloromethyl (dimethyl) silane) was added and cooled to 3°C. The mixture was filtered and washed with anhydrous ethanol and pure water for 3 times, dried at 30°C and 1kPa for 12 hours, and then placed in n-hexane with a mass of 20 times that of chloromethyl (dimethyl) silane, and diallyltetramethyldisiloxane with an equal molar amount of chloromethyl (dimethyl) silane and divinyltetramethyldisiloxane platinum salt with a mass of 0.03 times that of chloromethyl (dimethyl) silane were added, stirred and refluxed at 70°C and 500r / min for 6 hours, and allowed to stand at 20°C and 1kPa for 4 hours to obtain a flame retardant;

[0040] (2) Preparation of photoinitiator: 4-chlorobenzophenone, potassium hydroxide, toluene and N-methylpyrrolidone were mixed at a mass ratio of 1:0.2:12:4, and then an equal molar amount of p-hydroxythiophenol was added to 4-chlorobenzophenone. The mixture was stirred at 10°C and 300 r / min for 30 min, placed in a high-pressure reactor lined with polytetrafluoroethylene and sealed, heated to 120°C and maintained for 3 h, and then continued to heat to 170°C and maintained for 3 h. After cooling to room temperature, the reactor was opened, and the reaction solution in the liner was added dropwise at a rate of 2 mL / min to 8% hydrochloric acid with a mass fraction of 8 times the mass of the reaction solution at 3°C ​​stirred at 500 r / min, and ultrasonicated at 40 kHz for 20 min. The mixture was filtered and washed with pure water and petroleum ether 5 times each, and dried at -1°C and 10 Pa for 6 h to obtain a photoinitiator.

[0041] (3) Polymerization: Hydroxyethyl acrylate, photoinitiator, dibutyltin dilaurate in a mass ratio

[0042] 1:0.3:0.2 is mixed evenly as a blocking mixed reagent; the flame retardant, poly(diethylene glycol adipate) PDEGA3000, and 1,6-hexanediol diacrylate are mixed evenly in a mass ratio of 1:1:4, stirred at 10°C, 300r / min for 12min, heated to 35°C, 0.2 times the mass of the flame retardant 4,4'-dicyclohexylmethane diisocyanate is added every 15min, and the degree of reaction is monitored until the measured isocyanate group content is 40% of the added isocyanate group content, and does not change after delayed reaction, heated to 65°C and 0.1 times the mass of the flame retardant is added every 15min to block the mixed reagent, the degree of reaction is monitored, and the reaction is stopped when the measured isocyanate group content is 0.1% of the added isocyanate group content, and naturally cooled to room temperature to obtain a polyurethane adhesive for copper clad laminates.

[0043] Example 2

[0044] A method for preparing a polyurethane adhesive for a copper clad laminate, the method for preparing the polyurethane adhesive for a copper clad laminate mainly comprising the following preparation steps:

[0045] (1) Preparation of flame retardant: Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate were dissolved in dioxane (70 times the mass of chloromethyl (dimethyl) silane) in a molar ratio of 1:1, and then sodium hydroxide (0.15 times the mass of chloromethyl (dimethyl) silane) was added, and the mixture was stirred at 77°C and 900 r / min for 7 hours in a nitrogen atmosphere, and 4% hydrochloric acid (150 times the mass of chloromethyl (dimethyl) silane) was added and cooled to 4°C, filtered and washed. The mixture was washed with anhydrous ethanol and pure water for 4 times, dried at 35°C and 1.5 kPa for 11 h, and then placed in n-hexane with a mass of 25 times that of chloromethyl (dimethyl) silane, and diallyltetramethyldisiloxane with an equal molar amount of chloromethyl (dimethyl) silane and divinyltetramethyldisiloxane platinum salt with a mass of 0.04 times that of chloromethyl (dimethyl) silane were added, stirred and refluxed at 75°C and 650 r / min for 5 h, and allowed to stand at 25°C and 1.5 kPa for 3.5 h to obtain a flame retardant;

[0046] (2) Preparation of photoinitiator: 4-chlorobenzophenone, potassium hydroxide, toluene and N-methylpyrrolidone were mixed at a mass ratio of 1:0.25:14:5, and then an equal molar amount of p-hydroxythiophenol was added to 4-chlorobenzophenone. The mixture was stirred at 20°C and 400 r / min for 25 min, placed in a high-pressure reactor lined with polytetrafluoroethylene and sealed, heated to 125°C and maintained for 3.5 h, and then continued to heat to 165°C and maintained for 3.5 h. After cooling to room temperature, the reactor was opened, and the reaction solution in the liner was added dropwise at a rate of 1.5 mL / min to 7% hydrochloric acid (mass fraction 7 times the mass of the reaction solution at 1°C) stirred at 400 r / min, and ultrasonicated at 35 kHz for 25 min. The mixture was filtered and washed with pure water and petroleum ether 4 times each, and dried at -5°C and 5 Pa for 7 h to obtain a photoinitiator.

[0047] (3) Polymerization: Hydroxyethyl acrylate, photoinitiator, and dibutyltin dilaurate were mixed evenly at a mass ratio of 1:0.25:0.15 as a capping mixed reagent; flame retardant, poly (diethylene glycol adipate PDEGA3000), and 1,6-hexanediol diacrylate were mixed evenly at a mass ratio of 1:1:5, stirred at 15°C, 400 r / min for 11 minutes, heated to 40°C, and 0.25 times the mass of the flame retardant 4,4' was added every 15 minutes. -dicyclohexylmethane diisocyanate, and monitor the progress of the reaction until the measured isocyanate content is 45% of the added isocyanate content and does not change after the delayed reaction, raise the temperature to 70°C and add 0.15 times the mass of the flame retardant end-capping mixed reagent every 15 minutes, monitor the progress of the reaction until the measured isocyanate content is 0.2% of the added isocyanate content, stop the reaction, and naturally cool to room temperature to obtain the polyurethane adhesive for copper clad laminates.

[0048] Example 3

[0049] A method for preparing a polyurethane adhesive for a copper clad laminate, the method for preparing the polyurethane adhesive for a copper clad laminate mainly comprising the following preparation steps:

[0050] (1) Preparation of flame retardant: Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate were dissolved in dioxane (80 times the mass of chloromethyl (dimethyl) silane) in a molar ratio of 1:1, and then sodium hydroxide (0.2 times the mass of chloromethyl (dimethyl) silane) was added. The mixture was stirred at 80°C and 1000 r / min for 6 h in a nitrogen atmosphere. 3% hydrochloric acid (200 times the mass of chloromethyl (dimethyl) silane) was added and cooled to 5°C. The mixture was filtered and washed with anhydrous ethanol and pure water for 5 times, dried at 40°C and 2kPa for 10 hours, and then placed in n-hexane with a mass of 30 times that of chloromethyl (dimethyl) silane, and diallyltetramethyldisiloxane with an equal molar amount of chloromethyl (dimethyl) silane and divinyltetramethyldisiloxane platinum salt with a mass of 0.05 times that of chloromethyl (dimethyl) silane were added, stirred and refluxed at 80°C and 800r / min for 4 hours, and allowed to stand at 30°C and 2kPa for 3 hours to obtain a flame retardant;

[0051] (2) Preparation of photoinitiator: 4-chlorobenzophenone, potassium hydroxide, toluene and N-methylpyrrolidone were mixed at a mass ratio of 1:0.3:16:6, and then an equal molar amount of p-hydroxythiophenol was added to 4-chlorobenzophenone. The mixture was stirred at 30°C and 500 r / min for 20 min, placed in a high-pressure reactor lined with polytetrafluoroethylene and sealed, heated to 130°C and maintained for 3 h, and then continued to heat to 170°C and maintained for 3 h. After cooling to room temperature, the reactor was opened, and the reaction solution in the liner was added dropwise at a rate of 2 mL / min to 8% hydrochloric acid with a mass fraction of 8 times the mass of the reaction solution at 3°C ​​stirred at 500 r / min, and ultrasonicated at 40 kHz for 20 min. The mixture was filtered and washed with pure water and petroleum ether 5 times each, and dried at -1°C and 10 Pa for 6 h to obtain a photoinitiator.

[0052] (3) Polymerization: Hydroxyethyl acrylate, photoinitiator, dibutyltin dilaurate in a mass ratio

[0053] 1:0.3:0.2 is mixed evenly as a blocking mixed reagent; the flame retardant, poly(diethylene glycol adipate) PDEGA3000, and 1,6-hexanediol diacrylate are mixed evenly in a mass ratio of 1:1:6, stirred at 20°C and 500r / min for 10min, heated to 45°C, 0.3 times the mass of 4,4'-dicyclohexylmethane diisocyanate of the flame retardant is added every 15min, and the degree of reaction is monitored until the measured isocyanate group content is 50% of the added isocyanate group content, and does not change after delayed reaction, heated to 75°C and 0.2 times the mass of the flame retardant is added every 15min to monitor the degree of reaction until the measured isocyanate group content is 0.3% of the added isocyanate group content, the reaction is stopped, and naturally cooled to room temperature to obtain a polyurethane adhesive for copper clad laminates.

[0054] Comparative Example 1

[0055] A method for preparing a polyurethane adhesive for a copper clad laminate, the method for preparing the polyurethane adhesive for a copper clad laminate mainly comprising the following preparation steps:

[0056] (1) Preparation of flame retardant: Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate were dissolved in dioxane (70 times the mass of chloromethyl (dimethyl) silane) in a molar ratio of 1:1, and then sodium hydroxide (0.15 times the mass of chloromethyl (dimethyl) silane) was added, and the mixture was stirred at 77°C and 900 r / min for 7 h in a nitrogen atmosphere, and 4% hydrochloric acid (150 times the mass of chloromethyl (dimethyl) silane) was added and cooled to 4°C, filtered, washed with anhydrous ethanol and pure water for 4 times, and dried at 35°C and 1.5 kPa for 11 h;

[0057] (2) Preparation of photoinitiator: 4-chlorobenzophenone, potassium hydroxide, toluene and N-methylpyrrolidone were mixed at a mass ratio of 1:0.25:14:5, and then an equal molar amount of p-hydroxythiophenol was added to 4-chlorobenzophenone. The mixture was stirred at 20°C and 400 r / min for 25 min, placed in a high-pressure reactor lined with polytetrafluoroethylene and sealed, heated to 125°C and maintained for 3.5 h, and then continued to heat to 165°C and maintained for 3.5 h. After cooling to room temperature, the reactor was opened, and the reaction solution in the liner was added dropwise at a rate of 1.5 mL / min to 7% hydrochloric acid (mass fraction 7 times the mass of the reaction solution at 1°C) stirred at 400 r / min, and ultrasonicated at 35 kHz for 25 min. The mixture was filtered and washed with pure water and petroleum ether 4 times each, and dried at -5°C and 5 Pa for 7 h to obtain a photoinitiator.

[0058] (3) Polymerization: Hydroxyethyl acrylate, photoinitiator, and dibutyltin dilaurate were mixed evenly at a mass ratio of 1:0.25:0.15 as a capping mixed reagent; flame retardant, poly (diethylene glycol adipate PDEGA3000), and 1,6-hexanediol diacrylate were mixed evenly at a mass ratio of 1:1:5, stirred at 15°C, 400 r / min for 11 minutes, heated to 40°C, and 0.25 times the mass of the flame retardant 4,4' was added every 15 minutes. -dicyclohexylmethane diisocyanate, and monitor the progress of the reaction until the measured isocyanate content is 45% of the added isocyanate content and does not change after the delayed reaction, raise the temperature to 70°C and add 0.15 times the mass of the flame retardant end-capping mixed reagent every 15 minutes, monitor the progress of the reaction until the measured isocyanate content is 0.2% of the added isocyanate content, stop the reaction, and naturally cool to room temperature to obtain the polyurethane adhesive for copper clad laminates.

[0059] Comparative Example 2

[0060] A method for preparing a polyurethane adhesive for a copper clad laminate, the method for preparing the polyurethane adhesive for a copper clad laminate mainly comprising the following preparation steps:

[0061] (1) Preparation of flame retardant: Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate were dissolved in dioxane (70 times the mass of chloromethyl (dimethyl) silane) in a molar ratio of 1:1, and then sodium hydroxide (0.15 times the mass of chloromethyl (dimethyl) silane) was added, and the mixture was stirred at 77°C and 900 r / min for 7 hours in a nitrogen atmosphere, and 4% hydrochloric acid (150 times the mass of chloromethyl (dimethyl) silane) was added and cooled to 4°C, filtered and washed. The mixture was washed with anhydrous ethanol and pure water for 4 times, dried at 35°C and 1.5 kPa for 11 h, and then placed in n-hexane with a mass of 25 times that of chloromethyl (dimethyl) silane, and diallyltetramethyldisiloxane with an equal molar amount of chloromethyl (dimethyl) silane and divinyltetramethyldisiloxane platinum salt with a mass of 0.04 times that of chloromethyl (dimethyl) silane were added, stirred and refluxed at 75°C and 650 r / min for 5 h, and allowed to stand at 25°C and 1.5 kPa for 3.5 h to obtain a flame retardant;

[0062] (2) Polymerization: Hydroxyethyl acrylate, 4-hydroxybenzophenone, and dibutyltin dilaurate were mixed at a mass ratio of 1:0.25:0.15 to form a capping mixed reagent; flame retardant, poly(ethylene glycol adipate) PDEGA3000, and 1,6-hexanediol diacrylate were mixed at a mass ratio of 1:1:5, stirred at 15°C, 400 r / min for 11 min, heated to 40°C, and 0.25 times the mass of 4,6-hexanediol diacrylate was added every 15 min. 4'-dicyclohexylmethane diisocyanate, and monitor the progress of the reaction until the measured isocyanate content is 45% of the added isocyanate content and does not change after the delayed reaction, raise the temperature to 70°C and add 0.15 times the mass of the flame retardant end-capping mixed reagent every 15 minutes, monitor the progress of the reaction until the measured isocyanate content is 0.2% of the added isocyanate content, stop the reaction, and naturally cool to room temperature to obtain the polyurethane adhesive for copper clad laminates.

[0063] Comparative Example 3

[0064] A method for preparing a polyurethane adhesive for a copper clad laminate, the method for preparing the polyurethane adhesive for a copper clad laminate mainly comprising the following preparation steps:

[0065] (1) Preparation of flame retardant: Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate were dissolved in dioxane (70 times the mass of chloromethyl (dimethyl) silane) in a molar ratio of 1:1, and then sodium hydroxide (0.15 times the mass of chloromethyl (dimethyl) silane) was added, and the mixture was stirred at 77° C. and 900 r / min for 7 h in a nitrogen atmosphere, and 4% hydrochloric acid (150 times the mass of chloromethyl (dimethyl) silane) was added and cooled to 4° C., filtered, washed with anhydrous ethanol and pure water for 4 times, and dried at 35° C. and 1.5 kPa for 11 h to obtain a flame retardant;

[0066] (2) Polymerization: Hydroxyethyl acrylate, 4-hydroxybenzophenone, and dibutyltin dilaurate were mixed at a mass ratio of 1:0.25:0.15 to form a capping mixed reagent; flame retardant, poly(ethylene glycol adipate) PDEGA3000, and 1,6-hexanediol diacrylate were mixed at a mass ratio of 1:1:5, stirred at 15°C, 400 r / min for 11 min, heated to 40°C, and 0.25 times the mass of 4,6-hexanediol diacrylate was added every 15 min. 4'-dicyclohexylmethane diisocyanate, and monitor the progress of the reaction until the measured isocyanate content is 45% of the added isocyanate content and does not change after the delayed reaction, raise the temperature to 70°C and add 0.15 times the mass of the flame retardant end-capping mixed reagent every 15 minutes, monitor the progress of the reaction until the measured isocyanate content is 0.2% of the added isocyanate content, stop the reaction, and naturally cool to room temperature to obtain the polyurethane adhesive for copper clad laminates.

[0067] Effect example

[0068] Table 1 below shows the performance analysis results of the flame retardant properties and tensile properties of the polyurethane adhesive for copper clad laminates using Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0069] Table 1

[0070]

[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the polyurethane adhesive for copper clad laminates prepared in the present invention has good flame retardant properties and tensile properties.

[0072] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the limiting oxygen index and tensile strength of Examples 1, 2, and 3 are higher than those of Comparative Example 1, which shows that the flame retardant obtained by reacting with diallyltetramethyldisiloxane has a longer silicon-carbon chain segment and a carbon-carbon double bond at the edge, which can participate in the polymerization of free radicals initiated by the photoinitiator, so that the carbon-carbon double bonds at the edge are cross-linked and polymerized, so that the main body forms a cross-linked network structure, thereby improving the tensile properties of the polyurethane adhesive for copper clad laminates, and the flame retardant is interspersed and combined in the structure of the main material, and it is easier to form a silicon dioxide layer at high temperature to isolate oxygen and heat, thereby improving the flame retardant properties of the polyurethane adhesive for copper clad laminates; From Examples 1 and 2 By comparing the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that the tensile strength of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which shows that compared with the direct use of 4-hydroxybenzophenone, when p-hydroxythiophenol and 4-chlorobenzophenone are reacted, p-hydroxythiophenol replaces the chlorine on 4-chlorobenzophenone to form p-hydroxyphenylthio. Sulfur is an electron-rich atom, and the donating property of the sulfur bond will affect the carbonyl group of the benzophenone body, thereby affecting the hydrogen abstraction ability of the benzophenone body. Secondly, the sulfide bond can be broken under ultraviolet light to produce two free radicals, which trigger the free radical polymerization of the unsaturated bond, thereby improving the response range, response speed and degree of free radical polymerization to ultraviolet rays, thereby improving the tensile properties of the polyurethane adhesive for copper clad laminates.

[0073] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a polyurethane adhesive for copper clad laminates, characterized in that: The method comprises the following preparation steps: (1) Chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate are reacted, and then reacted with diallyl tetramethyl disiloxane to obtain a flame retardant; (2) reacting 4-chlorobenzophenone and p-hydroxythiophenol to prepare a photoinitiator; (3) reacting a flame retardant, polyethylene glycol adipate and 4,4'-dicyclohexylmethane diisocyanate, and then capping with hydroxyethyl acrylate and a photoinitiator to prepare a polyurethane adhesive for copper clad laminates; The molecular structure of the flame retardant is as follows: ; The molecular structure of the photoinitiator is as follows: 。 2. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 1, characterized in that: The preparation method of the polyurethane adhesive for copper clad laminate comprises the following preparation steps: (1) Preparation of flame retardant: Dissolve chloromethyl (dimethyl) silane and tris (2-hydroxyethyl) isocyanurate in dioxane (60-80 times the mass of chloromethyl (dimethyl) silane), add sodium hydroxide (0.1-0.2 times the mass of chloromethyl (dimethyl) silane), stir at 75-80 ° C, 800-1000 r / min for 6-8 hours in a nitrogen atmosphere, add 3-5% hydrochloric acid (100-200 times the mass of chloromethyl (dimethyl) silane) and cool to 3- 5℃, filter and wash with anhydrous ethanol and pure water for 3 to 5 times, dry at 30 to 40℃, 1 to 2kPa for 10 to 12h, then place in n-hexane with a mass of 20 to 30 times of chloromethyl (dimethyl) silane, add diallyl tetramethyl disiloxane and a catalyst with a mass of 0.03 to 0.05 times of chloromethyl (dimethyl) silane, stir and reflux at 70 to 80℃, 500 to 800r / min for 4 to 6h, and stand at 20 to 30℃, 1 to 2kPa for 3 to 4h to obtain a flame retardant; (2) Preparation of photoinitiator: 4-chlorobenzophenone, potassium hydroxide, toluene and N-methylpyrrolidone were mixed in a mass ratio of 1:0.2:12:4 to 1:0.3:16:6, and then an equal molar amount of p-hydroxythiophenol was added to 4-chlorobenzophenone. The mixture was stirred at 10-30°C and 300-500 r / min for 20-30 min. After solvothermal reaction, 6-8% hydrochloric acid was added dropwise at a rate of 1-2 mL / min to the reaction solution at 0-3°C stirred at 300-500 r / min. The mixture was ultrasonicated at 30-40 kHz for 20-30 min, filtered and washed with pure water and petroleum ether for 3-5 times each, and dried at -10--1°C and 1-10 Pa for 6-8 h to obtain a photoinitiator. (3) Polymerization: Hydroxyethyl acrylate, photoinitiator, and dibutyltin dilaurate are mixed evenly in a mass ratio of 1:0.2:0.1~1:0.3:0.2 as a capping mixed reagent; flame retardant, polyethylene glycol adipate, and 1,6-hexanediol diacrylate are mixed evenly in a mass ratio of 1:1:4~1:1:6, stirred at 10~20℃, 300~500r / min for 10~12min, heated to 35~45℃, and 0.2~0.3 times the mass of the flame retardant is added every 15min. 4,4'-dicyclohexylmethane diisocyanate, and monitor the progress of the reaction until the measured isocyanate content is 40-50% of the added isocyanate content and does not change after the delayed reaction, raise the temperature to 65-75°C and add 0.1-0.2 times the mass of the flame retardant end-capping mixed reagent every 15 minutes, monitor the progress of the reaction until the measured isocyanate content is 0.1-0.3% of the added isocyanate content, stop the reaction, and naturally cool to room temperature to obtain the polyurethane adhesive for copper clad laminates.

3. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 2, characterized in that: The molar ratio of chloromethyl (dimethyl) silane, tris (2-hydroxyethyl) isocyanurate and diallyltetramethyldisiloxane in step (1) is 1:1:

1.

4. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 2, characterized in that: The catalyst in step (1) is divinyltetramethyldisiloxane platinum salt.

5. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 2, characterized in that: The method of the solvent thermal reaction in step (2) is as follows: placing in a high-pressure reactor lined with polytetrafluoroethylene and closing the seal, heating to 120-130°C and maintaining for 3-4 hours, further heating to 160-170°C and maintaining for 3-4 hours, cooling to room temperature and opening the reactor.

6. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 2, characterized in that: The model of the polydiethylene glycol adipate in step (3) is PDEGA3000.

7. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 2, characterized in that: The method for monitoring isocyanate groups in step (3) is as follows: accurately take an appropriate amount of sample, add acetone, dissolve it, add a certain amount of 0.1 mol / L acetone-di-n-butylamine solution, shake well and let it stand for a period of time. If necessary, it can be heated. Titrate with a standard hydrochloric acid solution. The end point is when the solution changes from blue to yellow. Bromocresol green is used as an indicator. Blank titration is performed. The formula for the unreacted isocyanate group content is as follows: w%=(V0-V)*c*4.202 / m; Where: V0---the volume of hydrochloric acid lost by the sample in the blank experiment, unit: ml; V---volume of hydrochloric acid lost by the sample, in ml; c---Concentration of hydrochloric acid standard solution, unit mol / L; m---sample mass, unit: g.

8. The method for preparing a polyurethane adhesive for copper clad laminate according to claim 2, characterized in that: When the polyurethane adhesive for copper clad laminate is used to prepare copper clad laminate, a 300-400W high pressure mercury lamp is used to irradiate 2-3cm above the surface of the coated polyurethane adhesive for 40-50s.

Citation Information

Patent Citations

  • Preparation method of flame-retardant UV-curable polyurethane acrylate adhesive

    CN113930210A

  • Curable composition and sealing material composition

    JP2004115575A

Cited By

  • Modified polyphenyl ether with high heat resistance and damp-heat aging resistance and preparation method of modified polyphenyl ether

    CN121851362A